Diagnostic and prognostic benefits of computed tomography coronary angiography using the 2016 National Institute for Health and Care Excellence guidance within a randomised trial. Issue 3 (27th August 2017) - Adamson, Philip D; Hunter, Amanda; Williams, Michelle C; Shah, Anoop S V; McAllister, David A; Pawade, Tania A; Dweck, Marc R; Mills, Nicholas L; Berry, Colin; Boon, Nicholas A; Clark, Elizabeth; Flather, Marcus; et al.
Abstract : Objectives: To evaluate the diagnostic and prognostic benefits of CT coronary angiography (CTCA) using the 2016 National Institute for Health and Care Excellence (NICE) guidelines for the assessment of suspected stable angina. Methods: Post hoc analysis of the Scottish COmputed Tomography of the HEART (SCOT-HEART) trial of 4146 participants with suspected angina randomised to CTCA. Patients were dichotomised into NICE guideline-defined possible angina and non-anginal presentations. Primary (diagnostic) endpoint was diagnostic certainty of angina at 6 weeks and prognostic endpoint comprised fatal and non-fatal myocardial infarction (MI). Results: In 3770 eligible participants, CTCA increased diagnostic certainty more in those with possible angina (relative risk (RR) 2.22 (95% CI 1.91 to 2.60), p<0.001) than those with non-anginal symptoms (RR 1.30 (1.11 to 1.53), p=0.002; pinteraction <0.001). In the possible angina cohort, CTCA did not change rates of invasive angiography (p=0.481) but markedly reduced rates of normal coronary angiography (HR 0.32 (0.19 to 0.52), p<0.001). In the non-anginal cohort, rates of invasive angiography increased (HR 1.82 (1.13 to 2.92), p=0.014) without reducing rates of normal coronary angiography (HR 0.78 (0.30 to 2.05), p=0.622). At 3.2 years of follow-up, fatal or non-fatal MI was reduced in patients with possible angina (3.2% to 1.9%%; HR 0.58 (0.34 to 0.99), p=0.045) but not in those with non-anginal symptoms (HR 0.65 (0.25 to 1.69), p=0.379). Conclusions: NICE-guided patient selection maximises the benefits of CTCA on diagnostic certainty, use of invasive coronary angiography and reductions in fatal and non-fatal myocardial infarction. Patients with non-anginal chest pain derive minimal benefit from CTCA and increase the rates of invasive investigation. Trial registration number: ClinicalTrials.gov: NCT01149590 ;post results.